A new species of genus Prosopigastra A. Costa (Hymenoptera: Crabronidae: Crabroninae) from China, with a key to the Chinese species - Zhao, Liyuan; Li, Qiang; Ma, Li (Zootaxa, 2021)
The Chinese species of Prosopigastra A. Costa (Crabronidae: Crabroninae) are reviewed, including one species previously recorded from China and two species newly recorded from there. A new species, Prosopigastra simpliclypeata from Xinjiang Autonomous Region, China is described and illustrated. A key to the Chinese species of Prosopigastra is provided.